Airspace Capacity Analysis of Adisutjipto Airport - Aprinia Kusumaningsih; Dewanti Dewanti; Imam Muthohar (Institut Teknologi Dirgantara Adisutjipto, 2020)
Flight operation delays occur if there are delays both on the ground and in the airspace. It happened while the demand for air traffic exceeded the available capacity. The aim of the study is to analyse the airspace capacity based on Air Traffic Controller’s workload to support safety, expeditious, and orderly flow of air traffic which are the responsibility of the ATC. Primary data in this analysis were obtained by observing the activities conducted by ATC when delivering services to the airspace sector for 1 hour during peak hours within 30 days. The secondary detailed used to help the study relate to the amount of flight during peak hours, weather conditions, and flight plans. The analytical method used to determine the airspace capacity shall be the Pessimistic Sector Capacity. The result indicated a theoretical capacity of 31 aircraft per hour and practical capacity of 25 aircraft per hour with ATC personnel working time of 33 minutes being included in the heavy load category.